2014
DOI: 10.3174/ajnr.a3945
|View full text |Cite
|
Sign up to set email alerts
|

Large-Volume Blood Patch to Multiple Sites in the Epidural Space through a Single-Catheter Access Site for Treatment of Spontaneous Intracranial Hypotension

Abstract: BACKGROUND AND PURPOSE: Spontaneous intracranial hypotension can be a therapeutic challenge to the treating physician. In this study, we present our experience with the administration of a large-volume blood patch to multiple sites in the epidural space through a single-catheter access site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…All 5 patients with a CSF leak underwent a large-volume epidural blood patch procedure through a single-catheter access site to multiple sites in the epidural space, as described previously. 11 Four patients exhibited improvement of their symptoms with this procedure. One of these patients pursued experimental treatment at another institution despite the improving symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 5 patients with a CSF leak underwent a large-volume epidural blood patch procedure through a single-catheter access site to multiple sites in the epidural space, as described previously. 11 Four patients exhibited improvement of their symptoms with this procedure. One of these patients pursued experimental treatment at another institution despite the improving symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Additional symptoms may include dizziness, tinnitus, vomiting, altered mental status, and behavioral changes. 10,11,16 Findings on routine brain CT and MRI scans help to confirm a clinical suspicion of SIH. …”
mentioning
confidence: 99%
“…Other cardinal symptoms reported are nausea and vomiting occurred in about half of patients [8, 47], always accompanied by neck pain stiffness [26], blurred vision [12], “visual” filed defects and diplopia [48], cough headache [30], facial pain or numbness [49], tinnitus [41], taste alternations [8, 47] and limb paresthesias [50] and transient third cranial nerve palsy [51]. Neurocognitive decline such as dementia [52, 53], behavioral changes [5456] and parkinsonism [57] also can be presented which is rarer but has also been report.…”
Section: Reviewmentioning
confidence: 99%
“…Intracranial hypotension is a well-recognized entity associated with CSF leakage [54]. Multiple imaging methods are highly applicative and valuable for suspicious CSF leakage diagnosis [34], while some matters are needed.…”
Section: Reviewmentioning
confidence: 99%
“…Finding multiple sites of CSF leaks in occasional patients complicates matters further. Some authors have reported innovative techniques with blood patching at multiple sites using a single catheter access3 or the use of percutaneous fibrin glue sealant 1. If a patient's symptoms remain disabling, and there is a clearly identified site of CSF leak, and all treatment measures have failed, it is worth considering surgery.…”
mentioning
confidence: 99%